Keanekaragaman Tumbuhan Berhabitus Pohon, Semak atau Perdu, serta Herba di Bantaran Sungai Kaligarang Kota Semarang - Fira Putri Nur Awwalia; Talitha Widiatningrum (Life Science, 2024)
The Kaligarang River is one of the longest rivers in Semarang which is widely used for various purposes over time, this river has changed towards sedimentation and erosion. Therefore, the existence of vegetatiton is important as an ecosystem balancer. The purpose of this study is to study environmental parameters and analyze the diversity of plants found in the Kaligarang watershed. This type of research includes exploratory research with a line plot sampling method (5 quadrant plots) measuring 1x1 meters for herbs, 5x5 meters for shrubs/shrubs, and 10x10 meters for trees in May 2023-May 2024. Research locations at Tinjomoyo station, Tugu Soeharto, and behind PDAM Tirto Moedal. The results showed that the soil types found were sandy loam, clay, and dusty clay; soil pH between 5.51-6.23; C-organic content 0.32-0.94%; light intensity between 2950-7610 lux; ambient temperature 38°C-45°C, and air humidity 24%-43% which means that the quality of the environment is quite supportive of plant growth quite well. The results of the calculation of plant species diversity (H') with tree habitus was found at station 1 was 0,69 (low) and the highest at station 3 was 0.97 (low); the lowest shrub at station 2 was 0.45 (low) and the highest at station 3 was 1.19 (medium); and the lowest herbaceous at station 1 was 1.25 (medium) and the highest at station 2 was 2.92 (medium). The conclusion from these results is that environmental factors and plant diversity values at each station are different.